Three-Dimensional Evaluation of the Mandibular Lingula on Cone-Beam Computed Tomographic Images in The Turkish Population - Unal Erzurumlu, Zerrin; Torul, Damla (Journal of Dentistry Indonesia, 2022)
Objective: The purpose of this study was to provide morphometric and anatomical data for mandibular lingula (Li) in The Turkish population using three dimensional-cone beam computed tomography (3D-CBCT) images. Methods: CBCT images of the patients taken between July 2020 and March 2021, were retrieved from the archival records. A total of 100 Li’s of 50 patients who met the criteria of this study were evaluated. The distances between the tip of the Li and ramal landmarks/occlusal plane were measured and the shape of the Li was evaluated on 3D-CBCT images. Results: CBCT images of the 50 patients (19 males and 31 females) with an age range of 18 to 56 years were included in this study. Significant differences were found for the measurements of right LP (p < 0.001), left LP (p = 0.003), right LOP (p = 0.016) and left LOP (p = 0.007) between genders. A significant difference was observed for LI (p = 0.024) between the left and right sides. Regarding the shape of the Li significant difference was found between the right and left sides (p = 0.003), while no significant differences were observed among genders on either both sides. Conclusion: This study contributes additional data to the literature about the location and morphology of the Li in Turkish subpopulation. These results provide a reference for the clinicians regarding the procedures involving mandibular ramus to perform maneuvers in safe margins.